The Influence of School Principals' Strategic Leadership, Supervisory Supervision, and Education Roadmap Policies on Teacher Performance in the Core Government Area of the Nusantara Capital City - Sandi, Obi; Nuphanudin, Nuphanudin; Trihantoyo, Syunu; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2026)
Teacher performance plays a crucial role in determining the quality of educational outcomes, as teachers are the primary actors in implementing the learning process in schools. In the context of educational reform and the development of the Indonesian Capital City (IKN), strengthening teacher performance becomes increasingly important to ensure the effectiveness of educational policies and learning quality in strategic national areas. Several factors are considered to influence teacher performance, including the principal's strategic leadership, supervisory supervision, and the implementation of educational roadmap policies that guide the direction of educational development. This study aims to analyze the influence of the principal's strategic leadership, supervisory supervision, and educational roadmap policy on teacher performance in the Core Government Area of the Indonesian Capital City. The study used a quantitative approach with a causal ex post facto design. The study population was 135 teachers with a sample of 100 respondents determined using the Slovin formula and proportional random sampling technique. The research instrument was a closed questionnaire with a four-level Likert scale that had been tested for validity and reliability. Data analysis used multiple linear regression with the help of SPSS version 22. The results showed that partially the principal's strategic leadership, supervisory supervision, and educational roadmap policy each had a significant effect on teacher performance. Simultaneously, the three independent variables also had a significant effect on teacher performance with a coefficient of determination of 59.7%, indicating that variations in teacher performance can be explained by these three variables, while the rest is influenced by other factors outside the research model.